Molecular imaging of carotid plaque vulnerability - Alonso, Angelika; Artemis, Dimitrios; Hennerici, Michael G. (Cerebrovascular diseases, 2015)
Background: Carotid endarterectomy (CEA) has been shown to be beneficial in patients with high-grade symptomatic carotid artery stenosis. Patients with high-grade asymptomatic stenosis may only exceptionally benefit from CEA during periods of increased plaque vulnerability. Imaging modalities to characterize unstable, vulnerable plaques are strongly needed for better risk stratification in these patients. Summary: Contrast-enhanced ultrasound (CEUS) is a novel and noninvasive technique capable to identify several surrogate markers of vulnerable carotid plaques. The use of specific ultrasound microbubbles allows a reliable detection of microulcerations due to an optimized visualization of the plaque-lumen border. As microbubbles are strictly intravascular tracers, the detection of individual microbubbles within the plaque corresponds to intraplaque neovessels. The accuracy of CEUS in the visualization of newly formed microvessels has been confirmed in histological studies on carotid endarterectomy specimens. Together with the formation of adventitial vasa vasorum, intraplaque neovascularization is a strong predictor for symptomatic disease. The phenomenon of late phase contrast enhancement is based on the adherence of microbubble-containing monocytes on inflamed endothelium. Recent studies suggest that late phase contrast enhancement may reflect endothelial inflammation or activation within carotid plaques. The development of conjugated microbubbles that bind to specific ligands such as thrombotic material or neovessels has led to the term ‘molecular imaging'. CEUS with microbubbles targeted to P-selectin and VCAM-1, key molecules in leukocyte trafficking, was used to detect an inflammatory plaque phenotype, whereas microbubbles coupled to the VEGF-receptor may allow for a detection of neovascularization. Even though imaging with targeted microbubbles is yet in an experimental stage, this technique can visualize active plaque reorganization with increased vulnerability leading to generation of arterio-arterial embolism. Key Messages: The use of contrast-enhanced ultrasound can be recommended to assess atherosclerotic carotid lesions at risk for rupture. Prospective clinical studies are needed to validate the use of CEUS in patients with high risks of recurrent large artery strokes. In particular, this applies to the detection of intraplaque neovascularization, a well-established marker in preclinical and observational studies, while the clinical significance of late phase contrast enhancement still needs to be determined.